Uses and gratifications of news portal among Malaysian youths [Kegunaan dan kepuasan portal berita dalam kalangan belia Malaysia] - Tiung L.K.; Meri A.; Nayan L.M.; Othman S.S. (Universiti Kebangsaan Malaysia Press, 2024)
The purpose of this exploratory study is to identify motivations and gratifications from the uses of news portals among Malaysia youths through three focus group discussions and a forum in social media that was carried out from March to May 2015. Findings reveal that the rise of the smartphones popularity has contributed tremendously to the youth's preference to access to the online news portal compare to television, newspapers, and radio. Friends influence and the usefulness of smartphones itself has contributed to the new trend of media usage by which saw it is easier for them to share and exchange information. The Malay and English mainstream newspapers news portal are informant preference choice. The main reasons behind informants choosing the news portal are because it is easy, fast, cost-saving, flexible, easy to access, leisure time activity, education, follow current issues, and uniqueness of the news portal itself. They are satisfied with the news portal because it is faster and easier to access to the additional information when its required through the search engine such as Google. The characteristics of the news portal itself that are linked to the video and related news emerge as the attraction to the youth beside it is easier to share the information with their friends through social media such as WhatsApp. For the university students, the difficulty of access to the traditional media in the campus encouraged them to choose news portal. The free wifi in the university also plays significant role why they prefer news portal. As for the working group, the time constraint is seen as the main factor contribute to the uses of online news. Overall it is seen that the information seeking behaviors is still there but the form of the news changed to approach that is much easier and cheaper. 2016, Universiti Kebangsaan Malaysia Press. All rights reserved.